Anti-continuum approach on odd solitons in binary discrete media with cubic-quintic nonlinearity - Taib, L. A.; Hadi, Morteza S.A.; Umarov, Bakhram A.; , (IOP Publishing Ltd., 2017)
The existence and stability of bright odd strongly localized modes in discrete binary media with cubic and quintic nonlinearities are investigated mainly by applying anti-continuum method. There are three different types of bright localized modes being studied; symmetric, antisymmetric and shifted odd modes. However, certain analytical analysis is carried out first applying the anti-continuum limit assumption to estimate initial excitations in the media. It can be deduced that, the quintic nonlinearity is a significant factor for stability in antisymmetric and shifted odd modes.